Investigating the in-vitro antimicrobial activities of sorghum [Sorghum bicolor (L.) Moench] phenolic extracts on liver abscess causing bacterial pathogens - Salih, Harith M.; Amachawadi, Raghavendra G.; Kang, Qing; Smolensky, Dmitriy; Perumal, Ramasamy; Bowser, Sarah-Sexton; Prasad, P. V. Vara; Nagaraja, T. G. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionLiver abscesses that occur in finishing cattle fed high-grain, low-roughage diets, are of significant economic concern to the feedlot industry. The causative agents include both Fusobacterium necrophorum subspecies (necrophorum and funduliforme), Trueperella pyogenes, and Salmonella enterica serotype Lubbock. Tylosin, a macrolide antibiotic, is supplemented in the feed to reduce liver abscesses. Because of the concern with emergence of potential antimicrobial resistance, there is a need to find antibiotic alternatives. The aim of our study was to investigate the efficacy of phenolic compounds extracted from black and brown sumac sorghum extracts on liver abscess causing bacterial pathogens.MethodsPhenolic compounds were extracted by 75% aqueous acetone and total phenolic content was determined spectrophotometrically. Muller-Hinton broth (for S. enterica and T. pyogenes), and anaerobic Brain–Heart infusion broth (for Fusobacterium) with and without sorghum extracts (1 mg GAE/mL) were used. Growth was measured at 24 and 48 hours to determine bacterial concentration. Micro-broth dilution method was used to quantify growth inhibition. ResultsPlant based phenolic compounds have the potential to be an antibiotic alternative to control liver abscesses. Sorghum [Sorghum bicolor (L.) Moench] grain phenolic compounds, have the potential to be one of these alternatives. DiscussionOur study demonstrated that the phenolic extracts of black and brown sumac sorghum exhibited antibacterial activities against the liver abscesses causing pathogens including both subspecies of F. necrophorum and T. pyogenes in a dose dependent manner, but not S. enterica. Sorghum phenolic compounds have the potential to be supplemented in the cattle feed to control liver abscesses.